Kelayakan Usaha Budidaya Benih Ikan Nila Di Balai Benih Ikan Sungai Kambat Kabupaten Barito Kuala - Arini Rama Hartati; Ilhamiyah, Ilhamiyah; Ana Zuraida (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2024)
Abstract: Research on the feasibility of cultivating tilapia seeds at the Kambat River Fish Seed Center (BBI) Food Security and Fisheries Service of Barito Kuala District aims to find out the technical aspects of cultivating tilapia seeds, knowing acceptance, profits and feasibility of tilapia seed cultivation business, and knowing the problems in tilapia seed cultivation. The sampling method used was the case study method, where respondents were selected from related parties who handle the tilapia seed cultivation business in BBI Sungai Kambat. The data collection methods used were observation, interviews, documentation and literature study. The data analysis used in this research is descriptive analysis and financial analysis. Based on research results for 6 months of production, a total cost of IDR 13,627,750 was obtained from fixed costs of IDR 5,352,750 and variable costs of IDR 8,275,000. The revenue obtained was IDR 18,760,000,- with profits obtained amounting to IDR 5,132,250,- the calculation of the R/C Ratio obtained was 1.37, indicating that the business of cultivating tilapia seeds in the BBI Kambat River, Food Security and Fisheries Service Barito Kuala Regency is efficient (feasible to run).